Blind Box and Transaction Uncertainty: A Review of Islamic Economic Law on Modern Consumptive Practices - Warmin Warmin; Cici Amelia Destriyanti Pratiwi; Sukriyadin Zebua; Fahrul Hidayat (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This research is motivated by the problems that occur in blind box buying and selling transactions, because sellers and producers in the blind box buying and selling concept only inform the series or theme of the box, which will be sold on their blind box platform, without providing detailed information about what is inside the box. The purpose of this study is to understand the mechanisms underlying blind box buying and selling practices and to examine the perspective of Islamic economic law on them. This type of research is field research conducted at Miniso Mall Ciputra Tangerang. With a qualitative approach. Primary data sources from interviews with sellers and buyers, and secondary data from books, journal articles, and other documents. Data collection techniques include observation, interviews, and documentation. Then the data is analyzed using descriptive analysis techniques. The results of the study indicate that the blind box practice at Miniso Mall Tangerang contains an element of uncertainty (gharar) because consumers do not know for sure the product obtained during the transaction. From the perspective of Islamic Economic Law, this practice needs to pay attention to the level of uncertainty that exists to avoid causing losses to consumers. The blind box phenomenon shows the relevance of Islamic economic studies to the increasingly developing modern business model. Therefore, the principles of transparency, fairness, and consumer protection must be the basis for ensuring that transactions remain in accordance with Sharia values.